Thermal Performance of Vernacular Stilt House in Palu City - Andi Jiba Rifai Bassaleng; Puteri Fitriaty; Nur Rahmanina Burhany; Fuad Zubaidi; Rosmiaty Arifin (Pusat Publikasi Nusantara, 2024)
The stilt house is one of vernacular architecture features in Indonesia. Several stilt vernacular houses persist until 70 to 100 years old in Palu City. Stilt house forms were proved to be adaptive to tropical climates. This research provides evidence of a thermally comfortable interior created by the vernacular stilt house of Palu City. The research was carried out in two stages: field measurement and thermal comfort value analysis, based on SNI 03-6572-2001 standards. Purposive sampling was used to determine the research sample for vernacular stilt houses. The selected stilt house is located on Anoa street No 57, North Tatura Ward, Palu City. Field measurement was performed to record the indoor and outdoor thermal condition of the sample house employing Hobo Onset U12-012 RH-Light data logger and Hobo H-22 microclimate station. The results show that the outdoor air temperature peak is 36.8°C with 45% humidity. Meanwhile, the indoor peak temperature on the 1st floor reached 32°C with 51% humidity. On the 2nd floor, there are five rooms with peak temperatures ranging from 29.5°C to 34.6°C with 53% to 64% humidity, indicating that each room has a different temperature performance. This condition is due to several parameters, such as ceiling height, roof shape, opening size, room layout, and room orientation. The result also showed that the indoor air temperature tends to be lower than the outdoor air temperature. Hence, it is indicated that the design strategies of the sample building are adaptive to the tropical warm and humid conditions of Palu.